PERLAKUAN AKUNTANSI TERHADAP MAIN PRODUCT DAN BY PRODUCT SERTA PENGARUHNYA TERHADAP LABA UMKM KOPI BUBUK ISTIMEWA - Susi Susanti; Eri Triharyati (Jurnal AkunStie (JAS), 2020)
This research huses descriptive equalitati veresearch. Special Ground Coffee UKM has not done by product accounting treatment. Where salesor profits from by-product shave not been included in the Profit/Lossreport. For this reason, there searc hersdescribe 4 accounting treatments that include sales or profit sfrom by-product sinto the financial statement sof the Special Ground Coffee UKM. There are 4 treatments thatare analyzed, namely 1) By-product streatedas other profit canincrease the total profit. For 2015 it canincrease profits by 30.44%, In 2016 it canincrease profits by25.53%, in 2017 it canincrease profits by3.37%, in 2018 it canincrease profits by 6.53% and in 2019 it can increase profits by 0.66%.2) Accounting treatment forby-product profi tincreases thema in product sales profit,whichcaninc rease the total profitin 2015 by 30.44%, 2016 by 25.53%, 2017 by 3.37% andin 2018 by 6.53%.3)The accounting treatment of by-product sales reduces the cost of goods soldf or the main products canin crease the total profit in 2015 by 57.81%,2016 by 61.33%, 2017 by 24.45%, 2018 by 29.27%, year 2019 canin crease profits by 19.31% from Rp.65,959,700 to Rp.81,742,100.4)The accounting treatmen tof by product profit reduces the total cost of producing the main product can in crease the total profit in 2015 by 30.44%, in 2016 by 25.53%, in 2017 by 3.37%, in 2018 by 6.53% from Rp.51,223,500 andin 2019 canin crease profits by 0.66%.